2013
DOI: 10.1103/physrevb.87.115124
|View full text |Cite
|
Sign up to set email alerts
|

Electron-phonon superconductivity near charge-density-wave instability in LaO0.5F0.5BiS2

Abstract: We discuss the electronic structure, lattice dynamics and electron-phonon interaction of newly discovered superconductor LaO0.5F0.5BiS2 using density functional based calculations. A strong Fermi surface nesting at k=(π,π,0) suggests a proximity to charge density wave instability and leads to imaginary harmonic phonons at this k point associated with in-plane displacements of S atoms. Total energy analysis resolves only a shallow double-well potential well preventing the appearance of static long-range order. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
227
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(247 citation statements)
references
References 27 publications
18
227
2
Order By: Relevance
“…The close proximity of superconductivity to a CDW instability may bring about peculiar states that may be chemically tuned and would in turn allow us to probe the nature of the soft phonons and the ground state properties. [7,8] Moreover, electronic correlations resulting from structural inhomogeneities may promote novel phases that are vital to understand the evolution from the normal to the superconducting state. It is the case in the BiS 2 superconductors that disorder can tune and induce new correlated electron phenomena and can lead to electron localization.…”
Section: Introductionmentioning
confidence: 99%
“…The close proximity of superconductivity to a CDW instability may bring about peculiar states that may be chemically tuned and would in turn allow us to probe the nature of the soft phonons and the ground state properties. [7,8] Moreover, electronic correlations resulting from structural inhomogeneities may promote novel phases that are vital to understand the evolution from the normal to the superconducting state. It is the case in the BiS 2 superconductors that disorder can tune and induce new correlated electron phenomena and can lead to electron localization.…”
Section: Introductionmentioning
confidence: 99%
“…Recent theoretical calculations have suggested that a quasi-one-dimensional character of the band dispersion provides a good Fermi surface nesting [28][29][30][31][32] . Some of them have proposed that an unstable phonon at q = (q, q, 0) corresponding to the Fermi surface nesting vector causes a CDW instability 29,30 . How the SC is related to this Fermi surface nesting has been argued vigorously [28][29][30][31][32][33][34][35] .…”
mentioning
confidence: 99%
“…Some of them have proposed that an unstable phonon at q = (q, q, 0) corresponding to the Fermi surface nesting vector causes a CDW instability 29,30 . How the SC is related to this Fermi surface nesting has been argued vigorously [28][29][30][31][32][33][34][35] . Meanwhile, the symmetry of the superconducting gap has also been investigated theoretically and experimentally.…”
mentioning
confidence: 99%
“…In some theoretical calculations, possible CDW that is caused by Peierls mechanism has been proposed. From these theoretical calculations in LaO 1-x F x BiSe 2 , following features are expected.(i) The instability against CDW formation is expected to develop alongdirection in the k space [44].(ii) This instability of CDW is enhanced at the F concentration of 0.5, where Fermi surfaces connect [34][35][36][37].(iii) A period of the predicted CDW is expected to be √2 times of the lattice constant a 0, which is corresponding to the nesting vector along direction.The observed supermodulation is consistent with features (i) and (ii). On the other hand, the observed period of about 5 times of the lattice constant a 0 is inconsistent with (iii).…”
mentioning
confidence: 88%
“…This higher T c remains at ambient pressure after as-grown polycrystalline samples are annealed under high pressure. These high-pressure effects indicate that the crystal structure of these materials is rather unstable against the external perturbations.Theoretical calculations also predicted electronic and structural instability against the formation of charge density wave (CDW) [34][35][36][37][38]. A calculation of band structures predicted due to nesting at the F concentration of x=0.5, where the Fermi surface connects at around (/2, /2) in the k space [34,35].…”
mentioning
confidence: 99%